ELASTIC-PLASTIC PERFORMANCE OF CALCRETE STABILISED UNBOUND MATERIAL FOR OPTIMISED USE IN PAVEMENT LAYERS IN NORTHERN NAMIBIA (Malaysian Journal of Civil Engineering, 2018)
To understand the performance limits and to provide reliable prediction performance of different calcrete and sand mixes, the Elastic-plastic performance model of calcrete stabilised unbound material for optimize use in pavement layers in northern Namibia was investigated through the use of short-term monotonic triaxial tests conducted in the laboratory. General aspects of the behaviour of unbound granular materials were investigated , and results obtained through the use pavement software revealed that pavement performances in Northern Namibia could be not only be improved by at least three folds, but will also significantly reduce long term construction costs. The Rubicon Tool box was used to also describe permanent-deformation behavior of such pavement.